1988
DOI: 10.1073/pnas.85.14.5046
|View full text |Cite
|
Sign up to set email alerts
|

Bypass and termination at apurinic sites during replication of single-stranded DNA in vitro: a model for apurinic site mutagenesis.

Abstract: Mutations produced in Escherichia coli by apurinic sites are believed to arise via SOS-assisted translesion replication. Analysis of replication products synthesized on depurinated single-stranded DNA by DNA polymerase Ill holoenzyme revealed that apurinic sites frequently blocked in vitro replication. Bypass frequency of an apurinic site was estimated to be 10-15%. Direct evidence for replicative bypass was obtained in a complete single-stranded -+ replicative form replication system containing DNA polymerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
35
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 34 publications
3
35
0
Order By: Relevance
“…3), whereas in vitro bypass of blocking lesions (2,(11)(12)(13)(14)(15)(16)(17)(18)(19) and in vitro UV mutagenesis (20 -22) can occur without these proteins. The report on umuC-independent UV mutagenesis in phage S13 (55) and the finding that umuC-independent UV mutagenesis is observed when a screening rather than selection procedure is used (56) support the view that UmuDЈC stimulates the mutagenic reaction, rather than being absolutely required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3), whereas in vitro bypass of blocking lesions (2,(11)(12)(13)(14)(15)(16)(17)(18)(19) and in vitro UV mutagenesis (20 -22) can occur without these proteins. The report on umuC-independent UV mutagenesis in phage S13 (55) and the finding that umuC-independent UV mutagenesis is observed when a screening rather than selection procedure is used (56) support the view that UmuDЈC stimulates the mutagenic reaction, rather than being absolutely required.…”
Section: Discussionmentioning
confidence: 99%
“…A prevailing hypothesis is that UmuDЈ, the active form of UmuD (7)(8)(9), along with UmuC are required to assist the DNA polymerase in replicating the damaged site (10). However, the nature of this assistance is not clear because purified DNA polymerases can bypass DNA lesions unassisted (11)(12)(13)(14)(15)(16)(17)(18)(19). Moreover, in an in vitro system for UV mutagenesis carried out with crude protein extracts (20,21) or with purified proteins (22), we have found that UV mutations were effectively produced in the absence of UmuDЈ and UmuC.…”
mentioning
confidence: 99%
“…Both in vivo and in vitro experiments indicate that insertion of a base opposite a lesion is not rate limiting but that extension from the mispaired terminus is (6,18). The two modifications of Pol III that appear to be required are inhibition of the 3'-*5' exonuclease activity of epsilon to prevent the complex from stalling at the mispaired terminus (54) and improving the ability of the polymerase to extend from the mispaired terminus (2,6,18). A number of lines of evidence support the idea that RecA and UmuDC are involved in performing these alterations: (i) overproduction * Corresponding author.…”
mentioning
confidence: 99%
“…Current theories of SOS mutagenesis postulate that mutations occur when Pol III replicates past DNA lesions. Since reconstituted Pol III holoenzyme is poor at synthesizing past lesions in vitro (18), it appears to have to be modified in vivo to allow translesion synthesis. Both in vivo and in vitro experiments indicate that insertion of a base opposite a lesion is not rate limiting but that extension from the mispaired terminus is (6,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation